(untitled) (International Journal of Engineering and Computer Science, 2017)
Nowadays, the use of biometric characteristics (e.g., palmprints, irises, fingerprints) is incrementing for individual recognition and many applications of biometrics are already available. Biometrics recognition has many advantages over the traditionally used methods (e.g., password, smart card), because biometric characteristics cannot be shared or forgotten, as it is inherently associated with the individual. The main focus of Biometrics authentication system is on revocability, security, privacy, accuracy and privacy. In this fast developing communication world, one of the essential requirement is security of biometrics information. In this paper, a biometric authentication system with 2-way security is being proposed, which basically concerns with user’s privacy, network security, trust issues, template protection, and accuracy. Encryption of biometric details is done twice. That’s why; we called the system two way secured. None of the extra information is being disclosed to any unsafe network or any server’s database about the biometrics or user. Two different encryption algorithms are used at the client and server side. Modified version of RSA algorithm, i.e., RSA-2 algorithm is used at one side which is a public key cryptography and other encryption algorithm used is private key cryptography, 3DES algorithm. No restrictions are possessed on the biometric data used in the proposed approach and it is also applicable for different biometrics (palm print, face, iris, and finger print). An additional layer of security in authentication is being provided by using two way encryption schemes when compared with existing systems.